Global Warming, Early Flowering, Increase In Allergy Cases And Ahpco To Improve The Indoor Air Quality - Nabarun Ghosh; Jeff Bennert; Constantine Saadeh (European Scientific Journal, ESJ, 2016)
Global warming exerts substantial effect on flora and fauna. Increasing greenhouse gases causing accelerated pollinosis and fungal spore production, two major aeroallergens causing asthma and allergies. Recent reports show that the Texas Panhandle residents suffering from allergy and asthma has increased since 2007 and is twice that of the state rate. Climate change has effect on aeroallergens and allergies (Anglin, 2014). Early onset of spring and flowering season have been evidenced all over the world.The increasing trends of total pollen amounts, changing pollen seasons, and increasing carbon dioxide indicate there should be an increase in allergies and severity. The increasing trend of aeroallergen production will result in more cases of allergies throughout the coming years. We have been analyzing the daily aeroallergen by using Melinex tape from the Burkard Volumetric Spore Trap. Exposed, stained Melinex tape was observed under a BX-40 Olympus microscope. 16-years’ aeroallergen data of Texas Panhandle revealed a gradual shift in aeroallergen index with the warmer climate and a shift in flowering seasons. A collaborative research between the West Texas A&M University and Air Oasis developed Advanced Hydrated Photo Catalytic Oxidation (AHPCO) Nanotechnology and Plasma Nanotechnology. We evaluated the AHPCO Nanotechnology as a safe and efficient way in reducing indoor aeroallergens, such as pollen, bacteria, fungal spores and hyphae, dust particles, fibers, animal dander and VOCs in the indoor air. There is an ongoing research to apply the AHPCO and Plasma Nanotechnology to develop commodities like air purification system, food preservation system, ice makers and cell phone sterilizers.